PROMOTING CHARACTER EDUCATION IN EFL CLASSROOM: USING CHILDREN'S LITERATURE AS TEACHING MATERIALS - Putri, Mentari Antika (2017)
This study investigated a teacher's strategies in integrating the notion of character education in EFL classroom using children's literature as teaching materials along with the teacher's awareness of the ideology embodied in the story. A qualitative study embracing the characteristic of case study was employed in this study. The basic frameworks of this study are relied on Campoy (1997), Edgington (2002), O'sullivan (2004) and Hollindale (1988) framework. This study revealed that the teacher employed several strategies namely cause/effect/far-reaching effect, perspective windows, what's your perspective?, comparison of noble and ignoble character, value inculcation and value analysis. It is also found that teacher was aware of the ideology and potential of the text as a medium to expose character education. Based on the findings, it is recommended teachers should be more aware of the ideology presented children's literature since it can help the teacher to be more aware of the potential of using fiction to utilize it as a medium to explore character education Penelitian ini bertujuan untuk menyelidiki strategi guru dalam mengintegrasikan pendidikan karakter di kelas bahasa Inggris sebagai bahasa asing menggunakan literatur anak sebagai materi pembelajaran dan juga menyelidiki kesadaran guru akan ideology yang terkandung di dalam cerita tersebut. Penelitian ini merupakan penelitian bersifat kualitatif yang mengangkat karakter dari studi kasus sebagai metode penelitian. Teori dasar pada penelitian ini mengacu pada Campoy (1997), Edgington (2002), O'sullivan (2004) and Hollindale (1988). Penelitian ini menunjukan bahwa guru yang menjadi subjek penelitian ini menggunakan beberapa strategi yaitu cause/effect/far-reaching effect, perspective windows, what's your perspective?, comparison of noble and ignoble character, value inculcation dan value analysis. Penelitian ini juga menemukan bahwa guru menyadari ideologi pada cerita dan potensinya untuk digunakan sebagai media pendidikan karakter. Berdasarkan temuan pada penelitian ini guru disarankan untuk lebih memperhatikan ideologi yang tersaji pada literatur anak karena hal itu dapat membantu guru untuk lebih mengenali potensi dari fiksi yang digunakan sebagai media untuk mengaplikasikan pendidikan karakter.